Personalized Therapy for Multiple Myeloma (Springer International Publishing, 2018)
This book provides the clinician with concise, practical guidance on risk stratification and therapeutic decision making in patients with multiple myeloma. In addition, the available clinical trial and research data are summarized into meaningful reviews and evidence-based recommendations for treatment are presented. The coverage encompasses all phases and forms of disease, including high-risk myeloma. Over recent decades, greater understanding of the biology of myeloma has fostered the development of new, more effective drugs, leading to remarkable improvements in survival. To continue this momentum, several recent prospective trials have aimed to identify further potential therapeutic targets or to evaluate various combinations of anti-myeloma agents. The increasing abundance of management options makes treatment decision making in different phases of disease. This book will offer the clinician valuable assistance in the choice and sequencing of therapies, highlighting the need for a personalized approach that reflects the growing recognition that myeloma is not one uniform disease.